Whole Lives : Shapers of Modern Biography - Whittemore, Reed, 1919-2012 (Book collections on Project MUSE., 2019)
Whittemore in this companion volume to Pure lives probes the often complex motives behind the relationships of modern biographers to their subjects. Examines among others, Thomas Carlyle, Leslie Stephen, Sigmund Freud, Leon Edel, and Richard Ellmann as biographers.